-5b+24=-8(b-6)+4b

Simple and best practice solution for -5b+24=-8(b-6)+4b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5b+24=-8(b-6)+4b equation:


Simplifying
-5b + 24 = -8(b + -6) + 4b

Reorder the terms:
24 + -5b = -8(b + -6) + 4b

Reorder the terms:
24 + -5b = -8(-6 + b) + 4b
24 + -5b = (-6 * -8 + b * -8) + 4b
24 + -5b = (48 + -8b) + 4b

Combine like terms: -8b + 4b = -4b
24 + -5b = 48 + -4b

Solving
24 + -5b = 48 + -4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4b' to each side of the equation.
24 + -5b + 4b = 48 + -4b + 4b

Combine like terms: -5b + 4b = -1b
24 + -1b = 48 + -4b + 4b

Combine like terms: -4b + 4b = 0
24 + -1b = 48 + 0
24 + -1b = 48

Add '-24' to each side of the equation.
24 + -24 + -1b = 48 + -24

Combine like terms: 24 + -24 = 0
0 + -1b = 48 + -24
-1b = 48 + -24

Combine like terms: 48 + -24 = 24
-1b = 24

Divide each side by '-1'.
b = -24

Simplifying
b = -24

See similar equations:

| -5a-27=-6(2a+10) | | (10x-1)+(4x+7)=90 | | (x-10)=7 | | -5+7(x-2)=-35+5x | | 60-(x+2x-2)=0 | | 5x-2=22+3x | | 6-9+66=30 | | 3(x-2)(x-2)=27 | | 6p+6=2+2p | | 6v+21=-3(3-7v) | | 5x-2=5(x-1) | | (9x+6)+(3x)=90 | | 12x+1000= | | 5p-2-3p=16 | | 12x^2+4x+4=0 | | 3x+60-2=0 | | -6(x+8)-45=2-53 | | 19-12=x/8 | | 14=x+(x*.08) | | 4x-15+2x+3=48 | | -4x-15=19 | | 2(x-8)=8x+20 | | -5n=13-3 | | 5x-2=-8x+24 | | -16+3n=4n+7n | | 5x+6=2x+36 | | 4z+8x=360 | | 5x+6=2x+37 | | n-3+7=10+7n | | 10x-12+10x+32=180 | | -12x=15 | | 5k+5=-2-3k+k |

Equations solver categories